2022
DOI: 10.3389/fevo.2022.967692
|View full text |Cite
|
Sign up to set email alerts
|

Wild Panax plants adapt to their thermal environment by harboring abundant beneficial seed endophytic bacteria

Abstract: The seed microbiome of crop wild relatives is a potential reservoir of beneficial traits that potentially improve their host plant resilience to fluctuating environments and pathogenic threats. Herein, we studied the seed microbiome of three species of the medicinal genus Panax (P. vietnamensis, P. japonicas, and P. stipuleanatus) collected from seven locations in Southwest China. We used qPCR and metabarcoding high-throughput sequencing to target both endophytic bacteria and fungi. Seed bacterial absolute abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…In addition to their hereditary potential, wild plants utilize the plant-associated microbiome to expand their environmental adaptability, nutrient utilization efficiency and tolerance to biotic and abiotic stresses ( Cordovez et al., 2019 ; White et al., 2019 ; Liu et al., 2022a ). The main members of the phytomicrobiome originate from the endosphere, phyllosphere and rhizosphere ( Singh et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their hereditary potential, wild plants utilize the plant-associated microbiome to expand their environmental adaptability, nutrient utilization efficiency and tolerance to biotic and abiotic stresses ( Cordovez et al., 2019 ; White et al., 2019 ; Liu et al., 2022a ). The main members of the phytomicrobiome originate from the endosphere, phyllosphere and rhizosphere ( Singh et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that fungi can release mechanical dormancy by biomechanically breaking the pericarp of Lepidium didymum ( Sperber et al., 2017 ). However, little is known about the relationships between beneficial and pernicous microorganisms (fungi and bacteria) and seed quality ( Liu et al., 2022 ).Some of microorganisms stimulated seed germination, seedling health and growth ( Shade et al., 2017 ; Del Carmen Orozco-Mosqueda et al., 2020 ; Liu et al., 2022 ). For example, wild Panax plants adapt to their thermal environment by harboring abundant beneficial seed endophytic bacteria ( Liu et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the relationships between beneficial and pernicous microorganisms (fungi and bacteria) and seed quality ( Liu et al., 2022 ).Some of microorganisms stimulated seed germination, seedling health and growth ( Shade et al., 2017 ; Del Carmen Orozco-Mosqueda et al., 2020 ; Liu et al., 2022 ). For example, wild Panax plants adapt to their thermal environment by harboring abundant beneficial seed endophytic bacteria ( Liu et al., 2022 ). Some of microorganisms caused seed deterioration, including for seeds retained the hard-seeded characteristic.…”
Section: Introductionmentioning
confidence: 99%